Correlations of synergistic effect of glucocorticoids on tacrolimus with CYP3A, MDR1 and PXR gene polymorphisms in pediatric patients receiving liver transplantation for malignancy and chronic liver disease (Indian Journal of Experimental Biology (IJEB), 2021)
Immune suppression after liver transplant for malignancy, such as hepatocellular carcinoma and end stage liver disease is done using immunosuppressant drugs like tacrolimus. As the immune system in children is not fully developed, combining immunosuppressants like glucocorticoids influence the efficacy and reduce the chances of transplant rejection, particularly in patients with gene polymorphism. However, whether interaction between glucocorticoid and tacrolimus is associated with CYP3A, MDR1, and PXR gene polymorphisms, remains unclear. Here, we explored correlations of synergistic effect of glucocorticoids on tacrolimus with CYP3A, MDR1 and PXR gene polymorphisms in pediatric patients receiving liver transplantation for malignancy and chronic liver disease. A total of 340 eligible children were divided into glucocorticoid (+) (n=148) and glucocorticoid () groups (n=192). They were given tacrolimus + mycophenolate mofetil, based on which glucocorticoid (+) group took prednisone acetate tablets for ≥12 months. The blood trough concentration of tacrolimus was detected by chemiluminescence microparticle immunoassay 1, 3, 6 and 12 months after medication, and blood drug concentration corrected by daily concentration/daily dose (C0/D) was calculated. CYP3A, MDR1 and PXR gene polymorphisms were analyzed using PCR-RFLP. GG, AG and AA genotypes of CYP3A were observed in 130, 166 and 44 cases, respectively. CC, CT and TT genotypes of MDR1 were found in 152, 142 and 46 cases, respectively. There were 252, 74 and 14 cases of WW, WM and MM genotypes of PXR, respectively. The distribution frequencies of GG and AG+AA genotypes had significant differences between the two groups. One month after medication, C0/D of tacrolimus of GG genotype in glucocorticoid (+) group significantly exceeded that of glucocorticoid () group. C0/D was significantly higher in glucocorticoid (+) group with AG+AA genotype1, 3, 6 and 12 months after medication (P